If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 40 = 2x + 4 Reorder the terms: 40 + 6x = 2x + 4 Reorder the terms: 40 + 6x = 4 + 2x Solving 40 + 6x = 4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 40 + 6x + -2x = 4 + 2x + -2x Combine like terms: 6x + -2x = 4x 40 + 4x = 4 + 2x + -2x Combine like terms: 2x + -2x = 0 40 + 4x = 4 + 0 40 + 4x = 4 Add '-40' to each side of the equation. 40 + -40 + 4x = 4 + -40 Combine like terms: 40 + -40 = 0 0 + 4x = 4 + -40 4x = 4 + -40 Combine like terms: 4 + -40 = -36 4x = -36 Divide each side by '4'. x = -9 Simplifying x = -9
| 6(k-74)-5=83 | | 6=4-w | | x+17=5x+5 | | 6=-3(d-9) | | 2(7x+8)-4=28 | | 288=X+0.06X | | t-7/3=3 | | 4x+31=x+7 | | 12/n=3 | | 4x+11=x+1 | | 2/3x5/6x | | 8-51nx=3 | | 5x-26=x+6 | | x+(x*0.3)=5540.12 | | (x+(x*0.3))=5540.12 | | (X*.4)+X=4250 | | (2*.4)+X=4250 | | X*5+9=34 | | 9X*.40+X=4250 | | 6y=4y+24 | | 2X*.5=4250 | | x^3+x^2+x-20=0 | | 5x-12=-2+5 | | Y+1(33)-28=21 | | 10n+50=5n-25 | | 3y^2+2x-1=0 | | 3x-5x-120=0 | | -6n+3=-9 | | 2x-44=4x-88 | | 4n+10=2n-5 | | N-6=21-8n | | 9x+10y=500 |